Correlation of Serum TNF -ALPHA & Interferon - Gamma Level with H & Y Scale of Parkinson's Disease - G, Varunkrishnan; MD DM, T. Prabhu; Kutbuddin Parawala MD, Burhanuddin (Journal of Neonatal Surgery, 2025)
Aim: The aim of the present study was to examine the relationship of Serum TNF-α and Interferon- γ level in Parkinson disease and Disease severity. Methods: This research was carried out among patients presented to Department of General Medicine, Vinayaka Mission’s Medical College, Karaikal over an 18-month period. A total of 44 individuals were part of the study. Results: Majority participants fall in the age group of 71-80. The age distribution range was 57-88, while the mean age of the participants was 73.16±8.80 years. The male: female ratio is approximately 2:1 in this study. Majority of participants belonged to moderate disability (65.9%) and minimum number of cases were in server or advanced disability (11.4%). Majority of participants belonged to grade 3(38.6%), which least number of participants belonged to grade 5(6.8%). 34 cases had hypertension, which is 77.3 % of the cases. 31 cases had DM-T2 which is 70.4 % of the cases. Conclusion: We concluded in our study that gene expression of INF-γ and TNF-α were higher in patient with Severe form of PD. But the P-Value of these inflammatory markers were not statistically significant. A multi-centric study cross- sectional study should be done for further study.